Problems And Handling Of Electronic Payment Systems In The Digital Era In Medan - Mei Hotma Mariati Munte; Jadongan Sijabat; Ardin Doloksaribu; Imelda, Imelda (Jurnal Ekonomi, 2024)
Electronic payment system failure refers to a situation where a payment process or financial transaction is not completed as expected. Transaction failure using an electronic payment system can be caused by various factors, which are generally categorized into technical, security, infrastructure, and operational aspects. Therefore, this study aims to investigate technical problems, lack of user understanding, user errors, third-party interference, and high transaction volume levels as causes of electronic transaction failures and delayed funds in electronic payment systems.the problems, and handling of electronic payment systems. For this purpose, an investigation was conducted into technical problems, lack of user understanding, user errors, third-party interference, and high volume levels. The respondents of this study were those who were qualified (Medan residents/have visited Medan), users of electronic payment systems and have experienced problems processing transactions with electronic payment systems. The questionnaire compiled using Google Form was sent to 120 users of electronic payment systems among students using WA and 93 of them returned it. The results of the study showed that barriers to use and risk barriers had a negative effect on interest in using. While value barriers, tradition barriers, privacy barriers, and facilitating conditions had a positive effect on interest in using electronic payment systems.